Enhanced pinning in high-temperature superconducting cuprate single crystals at low magnetic field - Monarkha, V.Yu.; Savina, Yu.A.; Timofeev, V.P. (Functional Materials, 2013)
Low density flux dynamics in Nd based cuprate (NdBa₂Cu₃O₇₋x) HTSC single crystals trapped in ≈1 Oe range DC magnetic fields were investigated for the first time. Complex measurements of time, temperature and field dependence of magnetization were performed. Using the results obtained and the Anderson-Kim model the normalized magnetization relaxation rate S and the averaged effective pinning potential U were calculated. We show a significant increase in the effective pinning potential in comparison with measurements performed in high magnetic fields for similar cuprate single crystals formerly. In a wide enough range of temperatures close to Tc (0.72≤ T/Tc≤ 0.93) it has been shown that the doping of NdBa₂Cu₃O₇₋x single crystals with calcium atoms leads to an increase of the averaged effective pinning potential with an insignificant decreasing of the critical temperature.